Simultaneous use of adzuki beans (Vigna angularis) flour as meat extender and fat replacer in reduced-fat beef meatballs (bebola daging) - Lee, Aslinah Nyuk Fong; Mat Yusoff, Masni; Mohammad Rashedi, Ismail Fitry (Springer, 2018)
Adzuki bean is high in protein and fiber with a potential to be used as meat extender and fat replacer in the meat product. Replacement of both the corn flour and fat with different percentages of adzuki beans flour (ABF) has successfully produced acceptable reduced fat meatballs. Meatballs with 100% (w/w) ABF replacement exhibited highest cooking yield and higher moisture content compared to meatballs without the flour, which indicates its ability to bind water. Increasing the ABF content also increased the hardness and chewiness of the meatballs, whilst decreasing their lightness and yellowness. Replacing the corn flour and fat contents with ABF has obviously decreased the fat and calorie contents of the meatballs, yet their protein and carbohydrate contents remained the same compared to control. The sensory test revealed that meatball samples with 25% (w/w) and 50% (w/w) ABF showed no significant difference compared to control but received highest overall acceptability among the panelists. This indicates that replacement of corn flour and fat with ABF especially at 50% (w/w) in the production of reduced fat meatballs resulted with better physicochemical properties and acceptable sensory compared to original meatballs.